2007
DOI: 10.1007/s00402-007-0404-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the short-term functional results after surface replacement and total shoulder arthroplasty for osteoarthritis of the shoulder: a matched-pair analysis

Abstract: At short-term follow-up, surface replacement as a technically less demanding technique provided only slightly inferior results to TSR. We therefore believe that CUP arthroplasty is a therapeutic option and can be recommended in patients with primary osteoarthritis when limited to strictly defined indications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
29
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 20 publications
3
29
0
4
Order By: Relevance
“…2,3,[12][13][14] Surface replacement is also suggested to be more practical in cases of proximal humeral deformity secondary to fracture mal-union. In such cases, insertion of a stemmed component may not be possible, or may require adjunctive humeral osteotomy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,3,[12][13][14] Surface replacement is also suggested to be more practical in cases of proximal humeral deformity secondary to fracture mal-union. In such cases, insertion of a stemmed component may not be possible, or may require adjunctive humeral osteotomy.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Humeral resurfacing compared to standard stemmed total shoulder arthroplasty (TSA) may also have socioeconomic implications, with resurfacing hemiarthroplasty needing shorter operative time, and shorter periods of inpatient treatment. 13 Resurfacing is also considered to be a safer procedure in the elderly population as there is minimal blood loss, and it avoids intramedullary reaming and cementation with their possible anaesthetic and medical complications. 14 Published results of resurfacing procedures have shown similar clinical outcomes to those of stemmed implants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that the results of stemmed shoulder implants are improved if the glenoid is replaced (Boyd et al 1990, Sperling et al 1998, Gartsman et al 2000, Radnay et al 2007, Buchner et al 2008, Burgess et al 2009). For resurfacing arthroplasty, there is controversy about whether a glenoid component must be implanted, and surgical access may be difficult (Burgess et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For osteoarthritis, overall promising results were published for total resurfacing and hemiresurfacing (Levy and Copeland 2001, 2004, Rispoli et al 2006, Pritchett 2011), but revisions have been reported for glenoid erosion, and the preoperative glenoid wear status has influenced the individual indication for glenoid replacement (Levy and Copeland 2001, 2004, Bailie et al 2008, Buchner et al 2008, Burgess et al 2009, Pritchett 2011). …”
mentioning
confidence: 99%